Effect of Long Sowning in Urine Cow (Auxin) and Number of Books on Growth of Thoughtful Bamboo Cuttings (Gigantochloa nigrociliata (Büse) Kurz.) - Aminuddin Aziza (Contributions of Central Research Institute for Agriculture, 2022)
The results showed that soaking time in cow urine and number of books did not show any interaction with all variables. Separately, the soaking time did not have a significant effect on all variables at all ages, but the treatment of the number of nodes had a significant effect on root growth and the percentage of live cuttings, number of roots, fresh weight of roots and dry weight of roots at the age of 77 – 100 dap, where the treatment 2 books got the best results. There is a strong correlation between the number of roots and other root growth variables and the percentage of living cuttings. The number of roots influences the growth and percentage of living cuttings, where the roots provide food for the plant. Continuous utilization without replanting results in reduced production and germplasm. Not many bamboo seedlings have been provided due to the length of time needed for nurseries. To overcome this, an effort is needed to accelerate the growth rate and increase the percentage of successful seedlings, namely by soaking the material in auxin ZPT contained in cow urine and the number of books. Cow urine is an alternative provider of auxin ZPT for the high cost of artificial ZPT.